India's Climate Diplomacy: Politics or Policy?(2014-2022) - Saha, Nivedita (Indian Journal of Political Science)
Climate change is a key challenges which poses existential threat to humankind and it has taken centre stage in the arena of international relations. This requires cooperation from major emitters on mitigation, adaptation of various rules and procedures by the states. India sought to play an agenda setting role of key concepts and ideas. Since the beginning of deliberations, the principle of equity and common but differentiated responsibilities remained central to India's climate politics. Its scope has broadened overtime, inducted not only the disparities amongst various nation states but also within the country. This article aims to critically explicate India's climate policies over the years, laying special emphasis on the climate initiatives adopted by the Modi government from 2014
Keywords: climate change, India's Climate, politics, policies, challenges